PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA BERLIAN BEAUTY CLINIC SAMARINDA - Weni Maulina (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
This study aims to determine the effect of product quality and service quality on customer satisfaction at Berlian Beauty Clinic Samarinda ,. The analytical tools used are descriptive analysis and quantitative analysis with the help of SPSS statistical software version 22. The sampling technique in this study used a saturated sampling technique (census), which is a method that takes all populations to become respondents in this study. The number of taking samples was 83. Derived from the Berlian beauty Clinic sample on A. Wahab Syahranie street No.199A Samarinda. Data collection used is the technique of observation, questionnaires, and literature writing. While the analytical tool used is multiple linear regression analysis. The results of the study concluded that the product quality variable (X1) with a significant value of 0.05 because tcount = 7.569> ttable = 1.990 and the sig = 0.000 <0.05. The results of this study concluded that the variable service quality (X2) with a significant value of 0.05 because tcount = 4.554> ttable = 1.990 and the sig = 0.000 <0.05. thus the service quality variable has a partial effect on customer satisfaction (Y).